Computational Social Networks Security and Privacy - Abraham, Ajith; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2012)
The study of computational social networks (CSNs) is an emerging interdisciplinary field, concerned with the intersection of social behavior and computer systems. With the increasing popularity of social networking sites such as Myspace and Facebook, issues such as stalking, identity theft, sexual predators, and employee conduct have all become highly-publicized concerns. Many questions have also been raised about the ethics regarding the storage, management, and sharing of data held by CSNs. This comprehensive text/reference is the second of three volumes that illustrate the concept of social networks from a computational point of view. The book contains contributions from a international selection of world-class experts, concentrating on topics relating to security and privacy (the other two volumes review Tools, Perspectives, and Applications, and Mining and Visualization in CSNs). Topics and features: Includes a thorough introduction to this exciting and blossoming field Presents the latest advances in security and privacy issues in CSNs, and illustrates how both organizations and individuals can be protected from real-world threats Discusses the design and use of a wide range of computational tools and software for social network analysis Describes simulations of social networks, and the representation and analysis of social networks, with a focus on issues of security, privacy, and anonymization Provides experience reports, survey articles, and intelligence techniques and theories relating to specific problems in network technology This authoritative work is a useful resource for researchers and developers involved in social network research and related issues. Postgraduate and senior undergraduate students will also find this a valuable reference for courses on CSNs.
Part I: Privacy and Trust -- Computational Social Networks: Security and Privacy -- Security, Privacy and Trust in Social Networks -- Blogging Around the Globe: Motivations, Privacy Concerns and Social Networking -- Privacy in Online Social Networks -- Privacy Settings in Online Social Networks as a Conflict of Interests -- A Reliability-Based Metric for Inferring Trust from Recommendations in Knowledge Sharing Networks -- Part II: Security and Applications -- Measurement Methods of User Behavior in Online Social Networks -- Exploring Influence and Interests among Users within Social Networks -- User Cooperation, Virality and Gaming in a Social Mobile Network: The Gedda-Headz Concept -- An Effective User-Driven Framework for Selection of Social Network Services -- Opinion Mining for Social Networking: An Approach and Impact -- Part III: Anonymity -- Providing Group Anonymity in Social Networks -- Anonymisation of Social Networks and a Rough Set Approach -- Behavioural Patterns and Social Networks in Anonymity Systems.
Keywords: Computer science; Computer Communication Networks; Database management; Computer Science; Computer Communication Networks; Database Management; User Interfaces and Human Computer Interaction; Computers and Society